Strengthening Transparency and Accountability in Bureaucracy to Enhance Public Trust - Fadli Mappisabbi (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
Transparency and accountability are essential principles in good governance. However, there are still many challenges in achieving transparency and accountability within bureaucratic environments. This study aims to: 1) investigate the level of information openness and decision-making processes in government agencies; 2) identify best practices for enhancing transparency and accountability in bureaucracy; and 3) analyze the impact of transparency and accountability on public trust in the government. This research employs a qualitative approach using case study methods. Data was collected through in-depth interviews, document analysis, and observations in several central and regional government agencies. The results indicate that most government agencies have not yet optimized the implementation of public information openness principles. Decision-making processes tend to remain closed. However, some agencies have demonstrated good practices in enhancing transparency and accountability, such as using information technology, community involvement, and implementing effective complaint systems. The study also found that higher levels of transparency and accountability in bureaucracy correspond to higher levels of public trust in the government. This research concludes that transparency and accountability are crucial prerequisites for government bureaucracy to build public trust. Systematic and sustained efforts are needed to strengthen transparency and accountability practices within bureaucratic environments.